PERBANDINGAN KARAKTERISTIK BAHAN BAKU DAN PULP KRASIKARPA (Acacia crassicarpa A. Cunn) UMUR 1 SAMPAI 4 TAHUN - Opik Taupik Akbar; Yeni Aprianis; Ruspandi (BRIN Publishing, 2019)
Krasikarpa wood (Acacia crassicarpa A. Cunn.) is one of the fast growing peatland species for pulp and paper production. Pulp and chemical properties of krasikarpa wood under 4 years old have not been studied intensively. This paper examines pulp and chemical properties of krasikarpa wood during 1–4 years growth. Wood samples were taken from peatland area of Industrial Plantation Forest, PT. Arara Abadi, Riau. Chemical content examined includes extractives content in the solubility of ethanol benzene, lignin, and cellulose contents, while pulp properties studied were basic density, pulp productivity, and wood consumption. Wood samples were cooked using kraft pulping method with 18% alkali active, 25% sulfidity, wood to liquor ratio of 1:4, and temperature of cooking at 165°C for 3 hours. Experiment was designed based on Completely Randomized Design. Results showed that the age factor had a significant effect on all aspects studied. Based on further testing of LSD (Least Significant Differences), the significant effects included: extractive content at 4 years old, cellulose and lignin at 1 years old, pulp yield at 1 year old, density at 4 years old, wood productivity, and wood consumption at age 1, 3, and 4 years. After two years, extractive content start to increase, the lignin and cellulose content start to stabilize, and the pulp yield start to decline. Wood consumption decreases with age, the older the tree age, the lower the wood consumption.